In vitro biocompatibility study approaches to evaluate the safety profile of electrolyzed water for skin and eye. (November 2019) - Sipahi, H; Reis, R; Dinc, O; Kavaz, T; Dimoglo, A; Aydın, A
Electrolyzed water (EW) is a widely used disinfectant agent with high oxidation–reduction potential (ORP). Although EW has been used in many areas, such as food hygiene, agriculture, and animal husbandry, the studies presented in the literature are not enough to clarify the toxic effects of EW. The aim of this study is, therefore, to produce EWs at different pH, ORP, and chlorine concentrations and to assess their safety in terms of toxicology. At the beginning of the study, the antimicrobial activity of the EW types with respect to bacteria and fungus was investigated. EWs below pH 7 were all effective in inactivating Enterococcus hirae, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans completely. In vitro studies of cell cultures revealed that different concentrations of EWs were not cytotoxic for the L929 cells under 10- to 80-fold dilutions. In addition, it has been determined that produced EWs did not have irritation potential, according to the in vitro EpiDerm ™, reconstituted skin irritation test in the frames of biocompatibility tests. For the mucous membrane irritation test, the hen's egg test-chorioallantoic membrane experiment was performed, and EWs were found to have no eye irritation. In conclusion, it has been shown that produced EWs with antimicrobial efficacy were found to be safe for skin and eye according to in vitro biocompatibility study studies. Thus, the establishment of a technological infrastructure for the EW production and the use of produced EW as an effective disinfectant in the food, medical, and agricultural areas should be encouraged.